ANALYSIS OF MEDICATION MANAGEMENT IN THE PHARMACY UNITS OF DISTRICT/CITY HEALTH DEPARTMENTS: LITERATURE REVIEW - Aldhi Solihin Abd. Karim; Indri Hapsari; Githa Fungie Galistiani (CV. Fahr Publishing, 2026)
In order to guarantee the availability, fair distribution, and sensible use of medications, drug management at the District/City Health Office Pharmacy Installation is essential. This study uses a literature review methodology to examine several national publications over the last five years in order to investigate various issues and difficulties in drug management at the District/City Health Office Pharmacy Installation. In order to complete the review process, literature pertinent to the subject of drug management in healthcare institutions was chosen using inclusion criteria. Using the terms medication management, pharmaceutical installation, and health office, ten publications were retrieved from Google Scholar and the Garuda Portal (Garda Rujukan Digital). According to the study's findings, planning and procurement, storage and distribution systems, recording and reporting techniques, supervision and assessment, budgetary concerns, and human resource difficulties are the primary obstacles. The implementation of an integrated drug logistics information system, the development of human resource capacity, and more regionally sensitive policies are the goals of improvement initiatives. The study's findings highlight the necessity of a more all-encompassing management approach to ensure the successful, efficient, and sustainable operation of pharmaceutical services at the District/City level.